Sample strategies for the assessment of the apparent diffusion coefficient in single large intracranial space-occupying lesions of dogs and cats - Chan, Tatjana; Richter, Henning; Del Chicca, Francesca (Frontiers in Veterinary Science, 2024)
Diffusion-weighted imaging is increasingly available for brain investigation. Image interpretation of intracranial space-occupying lesions often include the derived apparent diffusion coefficient (ADC) analysis. In human medicine, ADC can help discriminating benign versus malignant lesions in intracranial tumors. This study investigates the difference in ADC values depending on the sample strategies of image analysis. MRI examination including diffusion-weighted images of canine and feline patients presented between 2015 and 2020 were reviewed retrospectively. Patients with single large intracranial space-occupying lesions were included. Lesions homogeneity was subjectively scored. ADC values were calculated using six different methods of sampling (M1 – M6) on the ADC map. M1 included as much as possible of the lesion on a maximum of five consecutive slices; M2, five central and five peripheral ROIs; M3, a single ROI on the solid part of the lesion; M4, three central ROIs on one slice; M5, three central ROIs on different slices; M6, one large ROI on the entire lesion. A total of 201 animals of various breeds, gender and age were analyzed. ADC values differed significantly between M5 against M2(peripheral) (p < 0.001), M5 against M6 (p = 0.009), and M4 against M2(peripheral) (p = 0.005). When lesions scored as homogenous in all sequences were excluded, additional significant difference in three further sampling methods was present (p < 0.005). ADC of single, large, intracranial space-occupying lesions differed significantly in half of the tested methods of sampling. Excluding homogeneous lesions, additional significant differences among the sampling methods were present. The obtained results should increase awareness in the variability of the ADC depending on the sample strategies used.